Tree architecture: A strigolactone-deficient mutant reveals a connection between branching order and auxin gradient along the tree stem - Su, Chang; Kokosza, Andrzej; Xie, Xiaonan; Pěnčík, Aleš; Zhang, Youjun; Raumonen, Pasi; Shi, Xueping; Muranen, Sampo; Topcu, Melis Kucukoglu; Immanen, Juha; Hagqvist, Risto; Safronov, Omid; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Due to their long lifespan, trees and bushes develop higher order of branches in a perennial manner. In contrast to a tall tree, with a clearly defined main stem and branching order, a bush is shorter and has a less apparent main stem and branching pattern. To address the developmental basis of these two forms, we studied several naturally occurring architectural variants in silver birch (Betula pendula). Using a candidate gene approach, we identified a bushy kanttarelli variant with a loss-of-function mutation in the BpMAX1 gene required for strigolactone (SL) biosynthesis. While kanttarelli is shorter than the wild type (WT), it has the same number of primary branches, whereas the number of secondary branches is increased, contributing to its bush-like phenotype. To confirm that the identified mutation was responsible for the phenotype, we phenocopied kanttarelli in transgenic BpMAX1::RNAi birch lines. SL profiling confirmed that both kanttarelli and the transgenic lines produced very limited amounts of SL. Interestingly, the auxin (IAA) distribution along the main stem differed between WT and BpMAX1::RNAi. In the WT, the auxin concentration formed a gradient, being higher in the uppermost internodes and decreasing toward the basal part of the stem, whereas in the transgenic line, this gradient was not observed. Through modeling, we showed that the different IAA distribution patterns may result from the difference in the number of higher-order branches and plant height. Future studies will determine whether the IAA gradient itself regulates aspects of plant architecture.
Keywords: Plant Growth Regulators; regulace genové exprese u rostlin; Betula; Indoleacetic Acids; Gene Expression Regulation, Plant; regulátory růstu rostlin; bříza; Betula pendula; auxin distribution; laktony; strigolactones; stromy; Trees; Lactones; kyseliny indoloctové; tree architecture; branching modeling